Penurunan Body Dissatisfaction Pada Perempuan Dalam Masa Emerging Adulthood Dengan Gratitude Intervention - Ananta, Aliffia (Persona:Jurnal Psikologi Indonesia, 2016)
This study aims to reduce body dissatisfaction in women in the period of emerging adulthood with gratitude intervention. Subjects of this study consisted of two people experiencing body dissatisfaction. This study used a quasi-experimental methods. Data making assessment conducted by interview, observation, body shape questionnaire, and gratitude questionnaire. Statistically the result showed that there is no gratitude intervention can not reduce body dissatisfaction (p= 0,180 > 0,05), but descriptive analysis showed that gratitude intervention gave positive result by reducing body dissatisfaction. The characteristic of body dissatisfaction are not confidence, never satisfied with their body, comparing their self to others who has more ideal body, sensitive, have a need for support and happy to get a compliment.Keywords : body dissatisfaction, gratitude intervention